2020
DOI: 10.3390/medicina56010020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cardiac Repolarization Indices in Epilepsy Patients Treated with Carbamazepine and Valproic Acid

Abstract: Background and Objectives: Epilepsy patients have a higher risk of sudden unexplained death compared to the rest of the population. Cardiac repolarization abnormalities might be seen in epilepsy during interictal periods. We aimed to evaluate the changes in electrocardiography (ECG) parameters in generalized tonic-clonic seizure patients treated with carbamazepine or valproic acid (VPA) drug. Materials and Methods: A totally of 129 subjects (66 epilepsy patients, 63 healthy subjects) were enrolled in the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…Of additional notice, although CBZ is safe and effective in anti-convulsant activities, the unwanted events following CBZ treatment, such as hyponatremia, QT-interval prolongation, hyperprolactinemia, change in pitch perception and idiosyncratic reactions, have gradually emerged [ 5 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The effectiveness of CBZ in inhibiting the activity of ATP-sensitive K + (K ATP ) channels has also been demonstrated [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of additional notice, although CBZ is safe and effective in anti-convulsant activities, the unwanted events following CBZ treatment, such as hyponatremia, QT-interval prolongation, hyperprolactinemia, change in pitch perception and idiosyncratic reactions, have gradually emerged [ 5 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The effectiveness of CBZ in inhibiting the activity of ATP-sensitive K + (K ATP ) channels has also been demonstrated [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Asoğlu et al demonstrate that QT dispersion, QTcd (QT interval corrected for heart rate dispersion) and Pd (atrial depolarization dispersion) values are significantly higher in epileptic patients using carbamazepine and valproic acid than in the healthy control group. They also report that female patients using carbamazepine and male patients using valproic acid have QTcd values significantly higher compared to female population in valproic acid or male patients on carbamazepine [1].…”
Section: Discussionmentioning
confidence: 94%
“…A prolonged QT interval is suggestive of repolarization abnormalities; it can be associated with an increased risk of torsade de pointes (TdP), that can lead to ventricular fibrillation and sudden cardiac death (SCD) and it is considered a marker of arrhythmia [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,6 Because carbamazepine has the property of moderating the phase 4 depolarization of the pacemaker cells, it tends to suppress the rhythm aggravating bradycardia of a complete heart block. 7 Cardiac conduction problems are more commonly reported in old female patients, 8,9 however, there are also some cases noted in old male patients such as in the study done by Celik et al wherein a 2:1 atrioventricular block was observed in a 56-year old man who was given carbamazepine 400 mg/day for 15 months for treating temporal lobe epilepsy. 10 Although the majority of the reported cases of carbamazepine-induced arrhythmia are observed in old female patients, a few incidents have been reported in middle-aged and young patients.…”
Section: Discussionmentioning
confidence: 99%